The Implementation of Kurikulum Merdeka in English Subject at SMP Negeri 02 South Bengkulu - Aprila, Anja; Riswanto, Riswanto; Martina, Feny (Lembaga Riset dan Inovasi Almatani, 2024)
This research examines the implementation of the Merdeka Curriculum in English language instruction at SMPN 2 South Bengkulu using a qualitative descriptive method. The study focuses on understanding the processes, challenges, and strategies involved in adopting the curriculum, which emphasizes educational diversity and flexibility. Through observations, interviews, and documentation, the research reveals that SMPN 2 South Bengkulu has effectively integrated the Merdeka Curriculum, guided by the principles of Pancasila and the development of superior human resources, despite encountering some obstacles. Key findings include the importance of teacher preparation, where English teachers familiarize themselves with curriculum regulations, analyze learning outcomes, prepare teaching tools, and understand the principles of Merdeka Curriculum assessment. The study also highlights the implementation of the curriculum in classroom activities, from opening sessions to core interactions and closing evaluations. Finally, the research discusses the assessment methods used, including diagnostic, formative, and summative assessments, which are adapted to the students' competencies and needs. The findings suggest that while challenges exist, the Merdeka Curriculum offers a flexible and holistic approach to education, promoting the development of students' cognitive, affective, and psychomotor skills in a democratic learning environment.